Vertical distribution of water vapour for Martian northern hemisphere summer in Mars year 28 from Mars Climate Sounder - Lolachi, R; Irwin, PGJ; Teanby, NA (Elsevier, 2022)
We present, for the first time, retrievals of the vertical distribution of water vapour from Mars Climate Sounder (MCS) aboard Mars Reconnaissance Orbiter (MRO), an original goal of the mission compromised by channel filter performance issues. To work around this problem a two-stage retrieval has been developed and was applied to MCS observations for MY28 NH summer (Ls=111–173°, 26 September 2006 to 27 January 2007). Retrievals were consistent with observations by other instruments for both column abundances (e.g., peak NH summer column abundance of 70 pr. μm compared with 50 pr. μm in the literature) and vertical profiles. Other key results are nightside vertical profiles of water vapour (retrieved for the first time) and interaction of atmospheric water vapour with the aphelion cloud belt. Seasonal changes in the hygropause (a proxy for condensation level) are reflected in changes in the cloud belt. During late northern summer, when the hygropause level is high at the equator and tropics, the cloudbase is higher (increasing by ≈ 10 km from 25 to 35 km) and the belt is weaker.